The Cambridge companion to miracles - Twelftree, Graham H. (Cambridge ; New York : Cambridge University Press, 2011)
"The miracle stories of the founders and saints of the major world religions have much in common. Written by international experts, this Companion provides an authoritative and comparative study of miracles in not only Hinduism, Islam, Buddhism, Christianity and Judaism, but also, indigenous religions. The authors promote a discussion of the problems of miracles in our largely secular culture, and of the value of miracles in religious belief. The miracles of Jesus are also contextualized through chapters on the Hebrew Bible, classical culture to the Romans, Second Temple and early rabbinic Judaism and early Christianity. This book provides students with a scholarly introduction to miracles, which also covers philosophical, medical and historical issues"--
Introduction : miracle in an age of diversity / Graham H. Twelftree -- Part I. Fundamental issues -- ch. 1. What is a miracle? / David Basinger -- ch. 2. The meanings of miracles / Robert A. Larmer -- Part II. Miracles in antiquity and the Middle Ages -- ch. 3. Miracles in the Hebrew Bible / R. Walter L. Moberly -- ch. 4. Miracles in the Greek and Roman world / Robert Garland -- ch. 5. Miracles in Second Temple and early rabbinic Judaism / Lidija Novakovic -- ch. 6. The miracles of Jesus / Barry L. Blackburn -- ch. 7. Miracles in early Christianity / James Carleton Paget -- ch. 8. Miracles in the Middle Ages / Benedicta Ward -- Part III. Miracles and major religions -- ch. 9. Miracles in tradiional religions / Fiona Bowie -- ch. 10. Miracles in Hinduism / Gavin Flood -- ch. 11. Miracles in Islam / David Thomas -- ch. 12. Tales of miraculous teachings : miracles in early Indian Buddhism / Rupert Gethin -- ch. 13. Miracles in Christianity / Ralph Del Colle -- ch. 14. Miracles in Jewish philosophy / Kenneth Seeskin -- Part IV. Miracle today -- ch. 15. Issues in the history of the debates on miracles / Colin Brown -- ch. 16. Philosophers on miracles / Michael P. Levine -- ch. 17. Patient belief in miraculous healing : positive or negative coping resource? / Niels Christian Hvidt.
Includes bibliographical references and index.
Keywords: Miracles